Malaria Research Priorities in Yemen: Paving the Way for Malaria Elimination - Rashad Abdul-Ghani (Yemeni Journal for Medical Sciences, 2015)
Malaria represents a major health problem in Yemen, and it appears that the efforts devoted to its control and elimination only tackle the tip of malaria iceberg. There is an evident gap between research activities and control efforts reflected by the fact that efforts and funding allocation are mainly directed to control activities. Research on basic, clinical and epidemiological aspects of the disease, which could serve elimination efforts, is rather ignored. This can simply be observed by searching online scientific databases, where the majority of published articles are of researchers and post-graduate students. Therefore, organized and collaborative research activities intended to serve the efforts to eliminate the disease are urgently needed, with a fair allocation of funds between research and control activities. The present editorial highlights research priorities needed to pave the way for malaria elimination and the need for bridging the existing gap between research and control strategies.